A Case Study of Pilgrimage as Experiential Learning: Reflections of a Buddhist Pilgrim - Ki, Yen Ping (The international journal of religious tourism and pilgrimage, 2022)
This paper narrates my learnings as a pilgrim in India and Nepal based on an analysis of my response to different experiences and observations throughout the journey. The significant impacts of this experience on life were reflected using Kolb’s cycle of experiential learning. The learning process is described based on the four processes of the model: concrete experience, reflective observation, abstract conceptualisation, and active experimentation. It is believed that pilgrims are motivated to satisfy their needs as indicated in Maslow’s hierarchy of needs. This article also acknowledges some established key ideas from other pilgrimage scholars. However, this paper presents only the ideas and early findings of the impacts of this pilgrimage experience on life. The long-term effects of pilgrimage are yet to be explored in future studies.